Predictors and moderators of response to brief interventions among adolescents with risky alcohol and marijuana use. Issue 1 (1st December 2022) - Becker, Sara J.; Marceau, Kristine; Helseth, Sarah A.; Hernandez, Lynn; Spirito, Anthony
Abstract: Background: Brief interventions have shown promise in reducing adolescent alcohol and marijuana use. This manuscript presents a secondary analysis of a randomized trial that compared a brief parent motivational intervention (Family Check Up; FCU) to brief psychoeducation (PE) condition and found no effect of treatment condition on either binge drinking or marijuana use days. The current analyses explored whether the response to treatment may have varied as a function of six empirically-based baseline moderators and predictors: biological sex, age, race/ethnicity, mental health problems, parent-adolescent communication, and peer deviance. Methods: Data from the parent trial randomizing 102 parents to either the FCU ( n  = 51) or PE ( n  = 51) interventions were re-analyzed across four time points (baseline, 3-, 6-, and 12-months). Moderators and predictors were tested via a series of hierarchical linear models. Results: Parent-adolescent communication and peer deviance emerged as significant predictors of adolescent treatment response. Specifically, low-levels of parent-adolescent communication or peer deviance were associated with worse treatment response (i.e., significant increases in binge drinking days and marijuana use days) in the PE condition, but not in the FCU condition. Non-Hispanic Whites and girls had worse treatment response, regardless of treatment condition. Conclusions: The FCU condition appeared to mitigate risks of poor parent-adolescent communication and affiliation with deviant peers better than the PE condition. Clinical recommendations for decision-making around assignment to brief interventions are discussed.